Entre traumatisme, adaptation et résilience chez les policiers victimes de la décennie noire - BOUKERZAZA, Khaoula (Journal of Human Sciences, 2015)
Man has developed variety of strategies to resist stress, and they vary according to the individual on the one hand, and the laborious that subjected to the other hand, as well as the different profession that employs. Scientists have classified the most stressful occupations to the ones in which humans deal with each others. Among these professions is security agent who normally maintains security and ensures comfort for others whatever the circumstances. So, what are the strategies used by this category? And are these strategies vary according to different college that individuals belong to ?